2017
DOI: 10.1016/j.biopsych.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Inattention and Reaction Time Variability Are Linked to Ventromedial Prefrontal Volume in Adolescents

Abstract: BACKGROUND Neuroimaging studies of attention-deficit/hyperactivity disorder (ADHD) have most commonly reported volumetric abnormalities in the basal ganglia, cerebellum, and prefrontal cortices. Few studies have examined the relationship between ADHD symptomatology and brain structure in population-based samples. Herein, we investigate the relationship between dimensional measures of ADHD symptomatology, brain structure, and reaction time variability—an index of lapses in attention. We also test for associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 46 publications
8
36
0
Order By: Relevance
“…The current findings of hyperactivation of the insula during negative stimuli add to the evidence for an insula dysfunction in ADHD, but suggest that the sign of the activation deficit is contextdependent: the insula appears to be underactive in ADHD in the context of cognitive tasks that are typically more boring to these adolescents and hence subjectively "undersalient" (Cubillo et al, 2011;Rubia et al, 2007Rubia et al, , 2009bRubia et al, , 2011a, while during negative emotions, which are strongly salient for ADHD, the insula seems to be hyperactive. Current findings fit to a recent ADHD sMRI study with a large populationbased sample (Albaugh et al, 2017) Speculatively, only the acute pharmaceutical effect of MPH may lead to a "normalized" brain activation for emotional attention, that is, no differences from TD as shown for the group with long-term medication without MPH pause in Posner et al (2011aPosner et al ( , 2011b. However, contrasting findings exist for a "cool" attentional reorienting task showing "normalized" brain activation for the insula and striatum after one year of MPH and one week break before the study (Konrad, Neufang, Fink, & Herpertz-Dahlmann, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The current findings of hyperactivation of the insula during negative stimuli add to the evidence for an insula dysfunction in ADHD, but suggest that the sign of the activation deficit is contextdependent: the insula appears to be underactive in ADHD in the context of cognitive tasks that are typically more boring to these adolescents and hence subjectively "undersalient" (Cubillo et al, 2011;Rubia et al, 2007Rubia et al, , 2009bRubia et al, , 2011a, while during negative emotions, which are strongly salient for ADHD, the insula seems to be hyperactive. Current findings fit to a recent ADHD sMRI study with a large populationbased sample (Albaugh et al, 2017) Speculatively, only the acute pharmaceutical effect of MPH may lead to a "normalized" brain activation for emotional attention, that is, no differences from TD as shown for the group with long-term medication without MPH pause in Posner et al (2011aPosner et al ( , 2011b. However, contrasting findings exist for a "cool" attentional reorienting task showing "normalized" brain activation for the insula and striatum after one year of MPH and one week break before the study (Konrad, Neufang, Fink, & Herpertz-Dahlmann, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…The current findings of hyperactivation of the insula during negative stimuli add to the evidence for an insula dysfunction in ADHD, but suggest that the sign of the activation deficit is context‐dependent: the insula appears to be underactive in ADHD in the context of cognitive tasks that are typically more boring to these adolescents and hence subjectively “undersalient” (Cubillo et al, ; Rubia et al, ), while during negative emotions, which are strongly salient for ADHD, the insula seems to be hyperactive. Current findings fit to a recent ADHD sMRI study with a large population‐based sample (Albaugh et al, ) which found that dimensional, multi‐informant measures of ADHD symptomatology in adolescents and RT variability were negatively associated with ventromedial PFC volume, an area that regulates amygdala activity (Motzkin, Philippi, Wolf, Baskaya, & Koenigs, ).…”
Section: Discussionsupporting
confidence: 87%
“…NeuroImage 169 (2018) 395-406 (Langner and Eickhoff, 2013;Corbetta and Shulman, 2002) and these findings lend support to previous structural findings, which linked prefrontal anomalies to increased IRV (Albaugh et al, 2017). The cerebellum is thought to have a critical role in sustained attention (Habas et al, 2009;Stoodley, 2012;Buckner, 2013).…”
Section: O'halloran Et Alsupporting
confidence: 85%
“…Neurological and psychopathological research is increasingly revealing a dimensionality aspect to developmental disorders such as ADHD (Hudziak et al, 2007) and conceptualizing attention-related traits as existing along a continuum shifts the focus from diagnostic groups towards diagnostic dimensions (O'Halloran et al, 2017). For example, reduced ventromedial prefrontal gray matter volume was associated with increased IRV in adolescents with elevated ADHD symptoms (Albaugh et al, 2017). Therefore, it is plausible that the (disrupted) functional connectivity patterns related to IRV in ADHD may be apparent among those with subclinical attention difficulties.…”
Section: Irv and Adhdmentioning
confidence: 99%
“…Initial studies in the general population reported associations between the extent of gaming or the level of "internet addiction"-associated symptoms and gray matter volume in reward processing regions, including the striatum (Kuhn et al, 2011;Montag et al, 2017;Zhou et al, 2019), suggesting that progressive volumetric changes in this region may accompany the transition into IGD. With the advent of the Research Domain Criteria approach dimensional imaging approaches have been increasingly employed in normal and pathological populations to map associations between pathology-relevant symptom dimensions and progressive dysregulations in the underlying brain systems (Albaugh et al, 2017;Li et al, 2019).…”
Section: Supplemental Materials)mentioning
confidence: 99%